Peace and Conflict in a Changing World Key Issues in Peace Studies - Kim, Dong Jin; Mitchell, David; Wylie, Gillian (Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2024)
X, 224 p. 1 illus.